atToc159 is a selective transit peptide receptor for the import of nucleus-encoded chloroplast proteins - Smith, Matthew D. (The Rockefeller University Press, 2004)
The members of the Toc159 family of GTPases act as the primary receptors for the import of nucleus-encoded preproteins into plastids. Toc159, the most abundant member of this family in chloroplasts, is required for chloroplast biogenesis (Bauer, J., K. Chen, A. Hiltbunner, E. Wehrli, M. Eugster, D. Schnell, and F. Kessler. 2000. Nature. 403:203–207) and has been shown to covalently cross-link to bound preproteins at the chloroplast surface (Ma, Y., A. Kouranov, S. LaSala, and D.J. Schnell. 1996. J. Cell Biol. 134:1–13; Perry, S.E., and K. Keegstra. 1994. Plant Cell. 6:93–105). These reports led to the hypothesis that Toc159 functions as a selective import receptor for preproteins that are required for chloroplast development. In this report, we provide evidence that Toc159 is required for the import of several highly expressed photosynthetic preproteins in vivo. Furthermore, we demonstrate that the cytoplasmic and recombinant forms of soluble Toc159 bind directly and selectively to the transit peptides of these representative photosynthetic preproteins, but not representative constitutively expressed plastid preproteins. These data support the function of Toc159 as a selective import receptor for the targeting of a set of preproteins required for chloroplast biogenesis.